Prospects for the Development of Small Business and Entrepreneurship in the Digital Economy - Nodirovna, Mirzaeva Shirin; Bakhtiyorovich, Shaymanov Javlonbek; Ta'nakulovich, Toirov Kamoljon (American Journal of Economics and Business Management, 2022)
Business plays a special role in the mechanism of sustainable economic development, since it provides not only the realization of innovative potential, but also the creation of decentralized jobs, as well as additional revenues to budgets of different levels. This article covers prospects for the development of small business and entrepreneurship in the digital economy. The article provides a lot of accurate statistics and graphical concepts related to the industry.